Soil microarthropods alter the outcome of plant-soil feedback experiments - Kuťáková, Eliška; Cesarz, Simone; Münzbergová, Zuzana; Eisenhauer, Nico (Scientific reports, 2018)
Plant-soil feedback (PSF) effects are studied as plant growth responses to soil previously conditioned by another plant. These studies usually exclude effects of soil fauna, such as nematodes, soil arthropods, and earthworms, although these organisms are known to influence plant performance. Here, we aimed to explore effects of a model microarthropod community on PSFs. We performed a PSF experiment in microcosms with two plant species, Phleum pratense and Poa pratensis. We added a model microarthropod community consisting of three fungivorous springtail species (Proisotoma minuta, Folsomia candida, and Sinella curviseta) and a predatory mite (Hypoaspis aculeifer) to half of the microcosms. We measured seedling establishment and plant biomass, nematode and microbial community composition, microbial biomass, and mycorrhizal colonization of roots. Microarthropods caused changes in the composition of nematode and microbial communities. Their effect was particularly strong in Phleum plants where they altered the composition of bacterial communities. Microarthropods also generally influenced plant performance, and their effects depended on previous soil conditioning and the identity of plant species. Microarthropods did not affect soil microbial biomass and mycorrhizal colonization of roots. We conclude that the role of soil microarthropods should be considered in future PSF experiments, especially as their effects are plant species-specific.
Keywords: Phleum; Nematoda; hlístice; Arthropods; Mycorrhizae; zvířata; biomasa; Poa; půda; druhová specificita; Mites; mykorhiza; Oligochaeta; ekosystém; Species Specificity; Feedback, Psychological; Plant Roots; Ecosystem; Biomass; kořeny rostlin; Animals; půdní mikrobiologie; Soil Microbiology; feedback psychologický; členovci; Soil; roztoči